A Dihydroflavonoid Naringin Extends the Lifespan of C. elegans and Delays the Progression of Aging-Related Diseases in PD/AD Models via DAF-16. (3rd August 2020) - Zhu, Qing; Qu, Yuan; Zhou, Xiao-Gang; Chen, Jian-Ning; Luo, Huai-Rong; Wu, Gui-Sheng
Abstract : Naringin is a dihydroflavonoid, which is rich in several plant species used for herbal medicine. It has a wide range of biological activities, including antineoplastic, anti-inflammatory, antiphotoaging, and antioxidative activities. So it would be interesting to know if naringin has an effect on aging and aging-related diseases. We examined the effect of naringin on the aging of Caenorhabditis elegans ( C . elegans ). Our results showed that naringin could extend the lifespan of C . elegans . Moreover, naringin could also increase the thermal and oxidative stress tolerance, reduce the accumulation of lipofuscin, and delay the progress of aging-related diseases in C . elegans models of AD and PD. Naringin could not significantly extend the lifespan of long-lived mutants from genes in insulin/IGF-1 signaling (IIS) and nutrient-sensing pathways, such as daf - 2, akt - 2, akt - 1, eat - 2, sir - 2 . 1, and rsks - 1 . Naringin treatment prolonged the lifespan of long-lived glp - 1 mutants, which have decreased reproductive stem cells. Naringin could not extend the lifespan of a null mutant of the fox-head transcription factor DAF-16. Moreover, naringin could increase the mRNA expression of genes regulated by daf - 16 and itself. In conclusion, we show that a natural product naringin could extend the lifespan of C . elegans and delay the progression of aging-related diseases in C . elegans models via DAF-16.